2010
DOI: 10.1016/j.molcel.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

“Depupylation” of Prokaryotic Ubiquitin-like Protein from Mycobacterial Proteasome Substrates

Abstract: Summary Ubiquitin (Ub) provides the recognition and specificity required to deliver proteins to the eukaryotic proteasome for destruction. Prokaryotic ubiquitin-like protein (Pup) is functionally analogous to Ub in Mycobacterium tuberculosis (Mtb) as it dooms proteins to the Mtb proteasome. Studies suggest that Pup and Ub do not share similar mechanisms of activation and conjugation to target proteins. Dop (deamidase of Pup; Mtb Rv2112c/MT2172) deamidates the carboxyl-terminal glutamine of Pup to glutamate, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(164 citation statements)
references
References 32 publications
(59 reference statements)
4
160
0
Order By: Relevance
“…1C), as reported by other researchers. 11,12) We confirmed that the band contained Pup Mt by performing Western blot and LC-MS/MS analyses (data not shown). The results obtained for Dop Re were similar to those obtained for Dop Mt , but free Pup was not detected when Pup Re conjugated proteins were used as substrate (Fig.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…1C), as reported by other researchers. 11,12) We confirmed that the band contained Pup Mt by performing Western blot and LC-MS/MS analyses (data not shown). The results obtained for Dop Re were similar to those obtained for Dop Mt , but free Pup was not detected when Pup Re conjugated proteins were used as substrate (Fig.…”
Section: Resultssupporting
confidence: 56%
“…These peptidase activities were completely abolished when depupylase-inactive mutant Dop ReE10A was tested (data not shown). 11,28) Pup has a disordered structure and is not highly conserved among actinomycetes (Fig. 2B), 30,31) as indicated by the various Pup cleavage patterns generated by Dop.…”
Section: Characterization Of the Endopeptidase Activity Of Dopmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation could reflect the fact that the genome of S. coelicolor is nearly twice the size of those of M. tuberculosis and M. smegmatis. An inherent challenge in the identification of all pupylated proteins in S. coelicolor or any other actinobacterium is that pupylation is a reversible phenomenon (28). This consideration led us to carry out the proteomic analyses on lysates from mycelia in different phases of growth.…”
Section: Resultsmentioning
confidence: 99%
“…Proteasome accessory factor A (PafA), the Pup ligase, subsequently ligates the newly-formed side chain carboxylate to a lysine residue of the target protein (48). Pupylated proteins are guided into the proteasome through the binding of Pup to the proteasomal ATPase, which unfolds proteins prior to delivery into the proteasome core (49). Dop also functions as a depupylase to remove Pup from substrate proteins prior to proteasomal degradation (50).…”
Section: Validation Of Quantitative Proteomic Data By Qpcr-tomentioning
confidence: 99%